2013
DOI: 10.1155/2013/359763
|View full text |Cite
|
Sign up to set email alerts
|

A Six-Month Randomized Controlled Trial of Whole Soy and Isoflavones Daidzein on Body Composition in Equol-Producing Postmenopausal Women with Prehypertension

Abstract: Objectives. This paper reported the effects of commonly used whole soy foods (soy flour) and purified daidzein (one of the major isoflavones and the precursor of equol) on changes in anthropometric measurements and body composition in a 6-month double-blind, randomized, placebo-controlled trial among prehypertensive postmenopausal women who are also equol producers. Methods. 270 eligible women were randomized to either one of the three treatments: 40 g soy flour (whole soy group), 40 g low-fat milk powder + 63… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 46 publications
1
45
0
Order By: Relevance
“…In vitro as well as in vivo studies suggested soy as a potential therapeutic agent for reduction of fat mass and weight, by an increase of energy utilization (Vaughn et al ., ), for decreased fat accumulation and a loss of visceral adipose tissue (Yamori, ; Nachtigal et al ., ). Correlations with a lower body mass index, waist circumference and body fat mass were observed (Liu et al ., ). Supplementation with S‐equol in obese and overweight patients significantly improved long‐term glycaemic control and cardiovascular health by lowering glycohaemoglobin, LDL‐C and arterial stiffness (Usui et al ., ).…”
Section: Epigenetics In Therapy Of Hormonal Dysfunction In Womenmentioning
confidence: 97%
See 2 more Smart Citations
“…In vitro as well as in vivo studies suggested soy as a potential therapeutic agent for reduction of fat mass and weight, by an increase of energy utilization (Vaughn et al ., ), for decreased fat accumulation and a loss of visceral adipose tissue (Yamori, ; Nachtigal et al ., ). Correlations with a lower body mass index, waist circumference and body fat mass were observed (Liu et al ., ). Supplementation with S‐equol in obese and overweight patients significantly improved long‐term glycaemic control and cardiovascular health by lowering glycohaemoglobin, LDL‐C and arterial stiffness (Usui et al ., ).…”
Section: Epigenetics In Therapy Of Hormonal Dysfunction In Womenmentioning
confidence: 97%
“…However, others reported none of these effects (Azadbakht and Nurbakhsh, ; Baer et al ., ; Takahira et al ., ; Liu et al ., ). Differences in population characteristics, types of soy products, intervention period, methods used and microbial fluctuation in isoflavone degradation may be responsible for these discrepancies (Liu et al ., ). Epigenetic treatments during age‐related sex‐steroid hormone loss in menopause should also be assessed in terms of cognitive benefits, as a loss of oestrogen is correlated with cognitive decline, dementia and AD (Frick et al ., ; Winkler and Fox, ).…”
Section: Epigenetics In Therapy Of Hormonal Dysfunction In Womenmentioning
confidence: 97%
See 1 more Smart Citation
“…22 In brief, the participants were Hong Kong Chinese women aged 48 to 65 years, at least 1 year after menopause, with a mean systolic blood pressure higher than 120 mm Hg or a mean diastolic blood pressure higher than 80 mm Hg, and who produce equol (defined as 24-h urinary log 10 S-equolYtoYdaidzein ratio 9j1.75 after daidzein challenge). 22 In brief, the participants were Hong Kong Chinese women aged 48 to 65 years, at least 1 year after menopause, with a mean systolic blood pressure higher than 120 mm Hg or a mean diastolic blood pressure higher than 80 mm Hg, and who produce equol (defined as 24-h urinary log 10 S-equolYtoYdaidzein ratio 9j1.75 after daidzein challenge).…”
Section: Study Design Setting and Participantsmentioning
confidence: 99%
“…Subjects were excluded if they were on anti-hypertensive medication, hormone therapy or hypoglycemic agents in recent 3 months; medical history or presence of cardiovascular diseases, severe liver and renal diseases and malignancies in recent 5 years. More details regarding subjects recruitment were published elsewhere [18].…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%